If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5 + -2x = 49x Solving 5 + -2x = 49x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-49x' to each side of the equation. 5 + -2x + -49x = 49x + -49x Combine like terms: -2x + -49x = -51x 5 + -51x = 49x + -49x Combine like terms: 49x + -49x = 0 5 + -51x = 0 Add '-5' to each side of the equation. 5 + -5 + -51x = 0 + -5 Combine like terms: 5 + -5 = 0 0 + -51x = 0 + -5 -51x = 0 + -5 Combine like terms: 0 + -5 = -5 -51x = -5 Divide each side by '-51'. x = 0.09803921569 Simplifying x = 0.09803921569
| x/792=.88 | | 2a-30a+108=0 | | 4+7x=9x | | x/792=88 | | 20x+0.05=10x+0.07 | | x+(2x+0.60)+(x+0.02)=7.2 | | X(x)(x)+y=y+x(x)(x) | | 5+x/6=-1 | | 5f^2+10f=0 | | 1.4=c/1.4 | | y-4x+7=x+1 | | 1.9=r/0.3 | | 5+20=-5x | | 2(-5x)-7(x-4)=10 | | .2+.15m+.1=.35 | | 5c+21=3(c-4) | | 7(5-z)/6=-z | | y/17=10 | | -2y+14=4y-16 | | 5-2x=7x | | 4+0=4 | | 20-(2d-2)=40 | | X-3/x+2=0 | | 9x^2-4xy+6y^2+6x-8y+2=0 | | 5/x-9=-4 | | 2(2+-3)=6(5+2) | | 300x^2+200x-375=0 | | -8(5)=5(-8) | | -15/4+x/3=--41/12 | | 9=78*3.14 | | 8+15x-4=8x+100-5x | | x(3x-7)=120 |